Analysis of Using Learning Media in The Subject of Fiqih Grade VII at MTs N 1 Pontianak - Firmansyah, Firmansyah (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2023)
Education has the power to enhance understanding, awareness, and skills for changes in knowledge and attitudes. For instance, in the teaching of Fiqih, an educator certainly requires instructional media as an intermediary between themselves and the learners. Instructional media plays a crucial role in the learning process by stimulating learning interest and enhancing learning effectiveness. The subject of Fiqh in Islamic education helps learners comprehend Islamic laws and apply them in their daily lives. The use of instructional media in Fiqh can enhance learner engagement and enrich the learning experience, provided that the chosen media align with the learning objectives and support a proper understanding of Fiqh concepts. This research employs a qualitative approach with a descriptive method. To gather research data, interview techniques, observation techniques, and documentation techniques are used. The data analysis includes data collection, data reduction, data display, and verification or conclusion drawing. The results of this research are as follows: The instructional media used in the 7th-grade Fiqh subject at MTs N 1 Pontianak include human-based media, visual media such as whiteboards, books, images/photos, and audio-visual media such as InFocus projectors (slides/videos). The steps for using Learning media Of Subject Fiqih at MTs N 1 Pontianak generally comprise: preparation, implementation, and follow-up.